2021
DOI: 10.1111/iwj.13553
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 on wound care in Germany

Abstract: Recent studies showed that the COVID‐19 pandemic caused collateral damage in health care in terms of reduced hospital submissions or postponed treatment of other acute or chronic ill patients. An anonymous survey was sent out by mail to patients with chronic wounds in order to evaluate the impact of the pandemic on wound care. Sixty‐three patients returned the survey. In 14%, diagnostic workup or hospitalisation was cancelled or postponed. Thirty‐six percent could not seek consultation by their primary care ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…Schlager et al reported that in Germany the pandemic has not had a significant negative impact on the quality of ambulatory care dedicated to patients with DFU ( n = 63) [ 30 ]. Unfortunately, the authors only assessed the soft endpoints, such as the quality of life and the frequency of changing wound dressing.…”
Section: Discussionmentioning
confidence: 99%
“…Schlager et al reported that in Germany the pandemic has not had a significant negative impact on the quality of ambulatory care dedicated to patients with DFU ( n = 63) [ 30 ]. Unfortunately, the authors only assessed the soft endpoints, such as the quality of life and the frequency of changing wound dressing.…”
Section: Discussionmentioning
confidence: 99%
“…2. Resultant evolutionary not knee-jerk change 8 Understanding the complexity of swiftly evolving wound care practice in a peri-and post-pandemic world needs to be a priority to assess the consequences of COVID-19 as they develop. This should be undertaken to develop an evidence base and key principles for the rapid changes that are currently taking effect, and the serious implications for patients, families, and clinicians post-pandemic.…”
Section: E D I T O R I a Lmentioning
confidence: 99%
“…Além disso, 15,4% afirmaram que a úlcera piorou no que se refere ao aumento das dimensões, à profundidade, e ao exsudato 5 . Resultados diferentes foram obtidos no estudo da Alemanha, considerando que o atendimento ambulatorial presencial foi mantido no período de pandemia e não houve diferença significativa na frequência de troca de curativos (P= 0,67), nem na pessoa que realizou o cuidado da ferida (P= 0,39), inclusive não houve mudanças significativas na qualidade da ferida (P= 0,505) 10 .…”
Section: Tratamento De Pessoas Com Feridas Como Serviço Essencialunclassified
“…A adaptação ao modelo remoto pode não ser fácil para muitos pacientes. Esta dificuldade ficou comprovada na Alemanha ao constatar que nenhum paciente com lesão usou telemedicina para evitar o contato presencial no período da pandemia 10 .…”
Section: Atendimento Remoto Nos Serviços De Atenção a Pessoas Com Feridasunclassified